Systematic Risk in Energy Businesses: Empirical Evidence for the ASEAN - Vo, Duc Hong; Pham, Thach Ngoc (International Journal of Economics and Financial Issues, 2017)
This paper is conducted to provide an additional empirical evidence in relation to the estimates of equity beta for energy businesses in the ASEAN-5 including Vietnam, Thailand, the Philippines, Malaysia, and Singapore. Listed energy companies for the period from 2005 to 2015 are used. Quantile regression, together with the OLS and LAD, has been used. Findings from this paper indicate that: (i) as long as the OLS and the LAD approaches are adopted, estimates of equity beta are relatively consistent across various research periods; (ii) estimates of equity beta appear to vary substantial across different quantiles; and (iii) estimates of equity beta have appeared to vary across research periods. However, as an overall level across time and methods, a level of risk faced by a company in the energy sector is below the average of the level of risk for the entire market for the above nations. Keywords: Beta, Listed Energy Firms, Quantile regression, ASEAN JEL Classifications: G11; G18